Antioxidant Defence in Labeo rohita to Biotic and Abiotic Stress: Insight from mRNA Expression, Molecular Characterization and Recombinant Protein-Based ELISA of Catalase, Glutathione Peroxidase, CuZn Superoxide Dismutase, and Glutathione S-Transferase - Sonali Parida; Pramoda Kumar Sahoo (MDPI AG, 2023)
Fish possess numerous enzymatic antioxidant systems as part of their innate immunity. These systems have been poorly studied in Labeo rohita (rohu). The present study characterized and investigated the role of antioxidant genes in the defence mechanisms against two types of stressors, including infection and ammonia stress. Four key genes associated with antioxidant activity-catalase, glutathione peroxidase, glutathione S-transferase, and CuZn superoxide dismutase were successfully cloned and sequenced. These genes were found to be expressed in different tissues and developmental stages of rohu. The expression levels of these antioxidant genes in the liver and anterior kidney tissues of rohu juveniles were modulated in response to bacterial infection (Aeromonas hydrophila), parasite infection (Argulus siamensis), poly I:C stimulation and ammonia stress. Additionally, the recombinant proteins derived from these genes exhibited significant antioxidant and antibacterial activities. These proteins also demonstrated a protective effect against A. hydrophila infection in rohu and had an immunomodulatory role. Furthermore, indirect ELISA assay systems were developed to measure these protein levels in healthy as well as A. hydrophila and ammonia-induced rohu serum. Overall, this study characterized and emphasised the importance of the antioxidant mechanism in rohu's defence against oxidative damage and microbial diseases.